Vestibular schwannomas and papilledema without hydrocephalus: a case report - Calderón-Moreno, Roberto; Pérez Carrillo, Noé; Martínez-Manrique, José de Jesús (Frontiers in Oncology, 2025)
Vestibular Schwannomas are frequent tumors of the cerebellopontine angle, classically presenting with cochlear and facial nerve alteration. They tend to have histopathological and intratumoral degeneration seen on MRI, and can cause CSF obstruction with hydrocephalus with subsequent visual loss. We present a case of bilateral visual loss from papilledema, with no history of hydrocephalus or increased intracranial pressure. CSF analysis showed isolated hyperproteinorrachia with no sign of infection or meningitis. This case report reviews current understanding of CSF physiology, including flow within the optic nerve sheath, which is a CSF reservoir with outflow through the complex glymphatic system. Multiple aquaporins regulate optic nerve CSF flow, responsible for the intense metabolic product washdown from the retinal apparatus. Aquaporin activity is susceptible to up-regulation or down-regulation from CSF content, such as in the complexity of certain Vestibular Schwannomas, as seen on molecular and histopathological analysis in other studies.